2023
DOI: 10.1002/ece3.10002
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of mycorrhization rates in a tree diversity experiment

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…At our experimental site, trees consistently preferred one mycorrhizal type but also exhibited mycorrhization of the opposite type, with rates varying throughout the season (Ferlian et al, 2021;Heklau et al, 2021Heklau et al, , 2023. Mycorrhizal spillover effects from neighbouring host tree species may affect EM and AM synchrony (Dickie et al, 2001), altering mycorrhization rates and fungal composition at the community level (Heklau et al, 2023), which could potentially lead to the observed positive effects of mycorrhizal type mixing.…”
Section: Mycorrhizal Types Modulate Drought Responsesmentioning
confidence: 83%
“…At our experimental site, trees consistently preferred one mycorrhizal type but also exhibited mycorrhization of the opposite type, with rates varying throughout the season (Ferlian et al, 2021;Heklau et al, 2021Heklau et al, , 2023. Mycorrhizal spillover effects from neighbouring host tree species may affect EM and AM synchrony (Dickie et al, 2001), altering mycorrhization rates and fungal composition at the community level (Heklau et al, 2023), which could potentially lead to the observed positive effects of mycorrhizal type mixing.…”
Section: Mycorrhizal Types Modulate Drought Responsesmentioning
confidence: 83%
“…Even though trees can interact with different types of mycorrhizal fungi simultaneously (Heklau et al, 2021(Heklau et al, , 2023, species have a preferred type of mycorrhizal partner (Brundrett & Tedersoo, 2018) and, thus, they are classified depending on the mycorrhizal host types as arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) trees.…”
Section: Introductionmentioning
confidence: 99%
“…Chestnut trees develop mycorrhizal symbiosis with arbuscular mycorrhizal fungi (AMF) [20]. Arbuscular mycorrhiza (AM) was reported in the roots of seedlings of A. hippocastanum and A. pavia [12], in the roots 2-to 3-year-old A. hippocastanum plants [21,22] and in the roots of mature trees of A. hippocastanum L. [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…So far, no long-term observations (lasting for several growing seasons) of mycorrhizal colonization of mature A. hippocastanum roots have been conducted. The seasonality of mycorrhizal colonization of A. hippocastanum roots was only investigated in a field experiment with 2-3-year-old seedlings of this species in two growing seasons [22].…”
Section: Introductionmentioning
confidence: 99%